Levelized cost of energy: A new estimation considering GHG emissions - Mario Villone (Atlantic Review of Economics (ARoEc), 2018)
The aim of this paper is to enunciate a new way to estimate levelized cost of electric energy (LCOE), considering emission of greenhouse gases cost, by taking the theoretical cost of avoiding pollution as the emission cost. In this way, it would be comparable LCOE from different sources of electrical generation with different GHG emission, in addition, with this way to calculate it could be possible to determine more efficient Pigouvian taxes (knowing the full cost of avoiding emission) and it could be possible also to generate an Economic-Ecological optimization Models for the electrical generation.
Keywords: Q49; Q52; Q54; 330; Electricity; Levelized cost of energy; GHG; CCS